INVENTARISASI TUMBUHAN OBAT TRADISIONAL DI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU SEBAGAI RANCANGAN BUKU SAKU KEANEKARAGAMAN HAYATI - Gival Giovani; Yuslim Fauziah; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research was conducted to inventory the types of traditional medicinal plants in the Sub-district Peranap Indragiri Hulu Regency on 9-25 March 2018. This research consists of two stages. The first is collecting data of medicinal plant species in the sub-district Peranap by survey method and snowball sampling technique by determining the key respondents (interview and field observation). Data were analyzed by descriptive. The second stage is the design of pocket book biodiversity of traditional medicinal plants from the results of research. The study found 106 plant species from 54 plant families with the largest number of species available in the family Lamiaceae and Zingiberaceae that is 7 species. A total of 74 species are used to treat diseases of the digestive system. Part of medicinal plant which is used is leaf (47,9%), way of processing plant which is widely used that is boiled (42,5%), then how to use medicine which is widely used that is drunk (59, 8%). Of the 106 species of plants found there are 7 types of potential (species of plants that nutritious and not widely known to the public) in Sub-District Peranap. Based on the analysis of the potential of senior high school biology syllabus, there are 8 Basic Competencies and Science of junior high school 7 Basic Competence related to the result of research designed to be a learning supplement in the form of pocket book on the material of biodiversity utilization effort.Keywords: Inventory, Medicinal Plant, Sub-district Peranap, Pocket Book.